CARBOHYDRATES CONTENT IN JERUSALEM ARTICHOKE TUBERS DURING VEGETATION - N. S. Levina; Yu. V. Tertyshnaya; I. A. Bidey; O. V. Elizarova (Сельскохозяйственные машины и технологии, 2017)
Jerusalem artichoke (Helianthus tuberosus L.) is rich in vitamins, carbohydrates, fiber. Tubers of Jerusalem artichoke consist valuable  substance inulin, which has a complex of health properties. Breeders create new hybrids and varieties of Jerusalem artichoke to increase the content of nutrients, productivity and climate resilience. The authors analysed moisture content, dry residue and fractional  composition of carbohydrates in the tubers of Jerusalem artichoke  varieties Skorospelka and Sireniki and the hybrids PBB and PBK in  various phases of vegetation. In the flowering stage the moisture of  the tubers of the investigated varieties was in the range of 77.2-81.3 percent, the value of dry residue of nutrients was 18.7-22.8 percent. The greatest number of non-reducing and total sugars in  the flowering stage contained in the tuber varieties of Sireniki and was equaled 78.3 and 61.8 percent, respectively. A similar analysis was conducted in the maturation phase. In this phase the solids  content slightly increased and amounted to 22.9-26.2 percent. Non- reducing sugars content, including inulin, increased in all the studied samples of Jerusalem artichoke. However, the greatest values of 72  percent were noted for variety Sireniki and hybrid PBK. The content  of inulin depends on the phase of the growing season and the  varietal characteristics of Jerusalem artichoke and the absence of decisive superiority of the hybrids.